Aksiologi Manusia dalam Perkembangan Pendidikan Islam (Perspektif KH. Ahmad Dahlan) - Dilla Fadhillah (Intiqad: Jurnal Agama dan Pendidikan Islam, 2022)
This study aims to analyze the axiological value of humans from the point of view of K.H. Ahmad Dahlan, who is a great figure in Islam and education in Indonesia. The research data were analyzed qualitatively. The data sources are articles on axiological values in philosophy and documents containing the thoughts of K.H. Ahmad Dahlan on humans and the development of Islamic education. The results of the analysis show that Dahlan's thoughts are in line with prophetic ethics which is part of axiology in the philosophy of Islam. The prophetic value consists of seven categories taken from the revelation of Allah SWT. These seven prophetic values include the value of worship, the value of sincerity, the value of the future, the value of mercy, the value of trust, the value of da'wah, and the value of tabsyir.